Growth pattern of Fortunian scalidophoran sclerites - Qin, Jiachen; Liu, Yunhuan; Shao, Tiequan; Liu, Mingjin; Zhang, Yanan (Frontiers in Earth Science, 2023)
Fortunian scalidophoran worms have shown high diversity, with 7 genera and species and 10 indeterminate forms. Current studies have mainly focused on morphology as well as early evolution, and studies on ontogeny have not been carried out due to the limited number of specimens. Here, we report a new material of an Orsten-type preserved Indeterminate Form 3 sensu Liu et al., 2019 from the Zhangjiagou section. Collected specimens of Indeterminate Form 3 sensu Liu et al., 2019 with different annulus widths indicate the presence of several ontogenetic stages. We found newly formed sclerites on the annulus of Indeterminate Form 3 sensu Liu et al., 2019 at different ontogenetic stages, suggesting that the sclerites of Indeterminate Form 3 sensu Liu et al., 2019 become more numerous in addition to increasing in size during growth. The size of the large sclerites may also increase as the worms grow, however, their number may not change.